Analisis Kesalahan Siswa dalam Menyelesaikan Soal Integral Bentuk Tak Tentu - Malasari, Tiur; Siregar, Fayyaza Aliya Nafisa; Syakira, Risya Indah; Asrizal, Salwa Silviyanti (Lembaga Yasin AlSys, 2024)
In this research, researchers analyzed students' errors in solving questions on the topic of indefinite form integrals. The purpose of this research is to determine the patterns of student errors that often occur when working on indefinite form integral questions, as well as the factors that cause them. The subjects in this research were 25 grade 11 high school students. This research was carried out by providing a test sheet in the form of essay questions on the subject matter of indefinite integrals, totaling 5 questions with 1 category of easy questions, 3 categories of medium questions, and 1 category of difficult questions. Based on the results of data analysis, it was obtained that for question number 1 (an easy category question), 100% of respondents answered correctly. Question number 2 (medium category question), 93.3% of respondents answered correctly. Question number 3 (medium category question) 54% of respondents answered correctly. Question number 4 (difficult category question), 46% of respondents answered correctly. Meanwhile, for question number 5 (difficult category question), only 20% of respondents answered correctly.